Electrical Discharge Drilling of Metal Matrix Composites with a Hollow Hexagonal Electrode. Issue 5 (September 2018) - Lin, Zhibiao; Guo, Zhongning; Jiang, Shuzhen; Liu, Guixian; Liu, Jiangwen
Aimed at the problems of the conventional electrical discharge machining of particle-reinforced aluminum matrix composites (PR-AMCs), a novel hollow hexagonal electrode has been employed and the influence of the electrode structure on the MRR has been investigated. In this study, 3-D model of the working medium fluid flow field has been established to study the structure effect of the hexagonal electrode. And a lot of single factor comparison experiments are carried out between the hexagonal hollow electrode and round hollow electrode. The effects of peak current, duty cycle, machining rotation speed and pulse width on the MRR of work-piece has been studied respectively. The Response Surface Method (RSM) is adopted to imitate the law of machining surface of the hexagonal hollow electrode. The theoretical and experimental results both show that the MRR of the work-piece can be improved remarkably by using a hexagonal hollow electrode. Moreover, according to the RSM, the maximum MRR of machining AMCs of the hexagonal hollow electrode is 225mm 3 /min, while the optimum combination of parameters that the peak current (12A), the duty cycle (0.75), machining rotation speed (900 r/min) and flushing pressure (1.5MPa) is exerted.